2015
DOI: 10.1111/acel.12315
|View full text |Cite
|
Sign up to set email alerts
|

Aging exacerbates hypertension‐induced cerebral microhemorrhages in mice: role of resveratrol treatment in vasoprotection

Abstract: Recent studies demonstrate that aging exacerbates hypertension-induced cognitive decline, but the specific age-related mechanisms remain elusive. Cerebral microhemorrhages (CMHs) are associated with rupture of small intracerebral vessels and are thought to progressively impair neuronal function. To determine whether aging exacerbates hypertension-induced CMHs young (3 months) and aged (24 months) mice were treated with angiotensin II plus L-NAME. We found that the same level of hypertension leads to significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
216
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(229 citation statements)
references
References 41 publications
(86 reference statements)
13
216
0
Order By: Relevance
“…Results of previous experimental studies by our laboratories (Toth et al ., 2015b), and by others (Wakisaka et al ., 2010a,b), identify oxidative stress as a critical factor contributing to hypertension‐induced MMP activation and pathogenesis of CMHs and demonstrate that high intraluminal pressure per se (via increased wall tension‐dependent cellular stretch) is a key stimulus for increased vascular production of ROS (Ungvari et al ., 2003; Springo et al ., 2015; Toth et al ., 2015b) that lead to MMP activation. To elucidate the likely mechanism contributing to the exacerbation of hypertension‐induced MMP activation in IGF‐1 deficiency, we compared pressure‐induced production of O2· in cerebral arteries isolated from IGF‐1‐deficient mice and their respective age‐matched controls using the redox‐sensitive dye dihydroethidium (DHE).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Results of previous experimental studies by our laboratories (Toth et al ., 2015b), and by others (Wakisaka et al ., 2010a,b), identify oxidative stress as a critical factor contributing to hypertension‐induced MMP activation and pathogenesis of CMHs and demonstrate that high intraluminal pressure per se (via increased wall tension‐dependent cellular stretch) is a key stimulus for increased vascular production of ROS (Ungvari et al ., 2003; Springo et al ., 2015; Toth et al ., 2015b) that lead to MMP activation. To elucidate the likely mechanism contributing to the exacerbation of hypertension‐induced MMP activation in IGF‐1 deficiency, we compared pressure‐induced production of O2· in cerebral arteries isolated from IGF‐1‐deficient mice and their respective age‐matched controls using the redox‐sensitive dye dihydroethidium (DHE).…”
Section: Resultsmentioning
confidence: 85%
“…We found that gait abnormalities (including a significant decline in regularity index, speed, and stride length; Fig. 2A–C, respectively) were significantly more severe in hypertensive IGF‐1‐deficient mice as compared to hypertensive control mice, suggesting that analysis of motor function status (e.g., deficit in interlimb coordination, temporal asymmetry) can predict the severity of CMH burden (Toth et al ., 2015b). Hypertension‐induced changes in base of support did not correlate with IGF‐1 status (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations